A Contrastive Analysis between English and Indonesian Adjectives in Report Text - David Gordon Gultom; Shinta Dwiana Sirait; Anita Sitanggang; Selviana Napitupulu; Asima Rohana Sinaga (Jurnal Scientia, 2022)
A Contrastive Analysis between English and Indonesian Adjective Clause is the focus of this work. Analyzing adjective clause and pointing out similarities and differences between English and Indonesian adjective clause are the study's main goals. This investigation is qualitative. The researchers started by gathering information from books on English and Indonesian grammar. Second, the researchers located them on all different kinds of adjective clauses. The collected and categorized data were finally examined. According to the analysis's findings, there were all different kinds of adjective clauses. The researchers were able to identify the similarities and differences in the data after analysis. Based on functional distinctions, whose, which, and that are employed in sentences in English but not in Indonesian